PERSEPSI AKUNTAN PRIA DAN AKUNTAN WANITA SERTA MAHASISWA DAN MAHASISWI AKUNTANSI TERHADAP ETIKA BISNIS DAN ETIKA PROFESI AKUNTAN - Murtanto Murtanto; Marini Marini (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
This research has two objectives. Firstly, observing the effect of gender differ-ence on perception of accountants and accounting students on business ethics and accountant's professional ethics. Secondly, observing which perception is better be-tween men and women both accountants and accounting students on business ethics and accountant's professional ethics. The sample are 192 respondents that consist of accountants and accounting students, in which the data collection used questionnaire.The test of hypothesis used Mann-Whitney U test and Mean. The result of the research shows there is not significantly differences between perception of men and women both accountants and accounting students on accountant's professional eth-ics, which is men accountants and accounting students had better perception about accountant's professional ethics. On business ethics there is differences perception between men and women accounting students, on the contrary between accountants both men and women has same perception about business ethics, but women ac-countants and accounting students had better perception about business ethics.Keywords: Business ethics, accountant's professional ethics, perception, accoun-tants, students, and gender